(3GdMGUd aj Yde GdejRGfs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdbfG djS jVQ GdEfSGf GdeMH dGSJjYGH Yde GdehGRjf s
(3BNQgG (B:s
(3aEfg jQi Cf LhgQ GdVQhQI gheQI GdYfUQ heQI GdhUdI GdJi Hjf GdaGYd hHjf GdYfUQ aGdcTa Yf Pdc jJVM GdMb Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B92 - (3U(B119s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B113 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs